RUANG PUBLIK BARU DAN PERUBAHAN SOSIAL: PEMANFAATAN INTERNET UNTUK ADVOKASI DAN DISEMINASI ISU PENUNDAAN PEMILU STUDI KASUS MAFINDO DAN DRONE EMPRIT - Rahman, Mila Amalia; Afifah, Zahra Nur; Ma’rifah, Iza; Laras Lestari, Dewi; Heryanto, Gun Gun; Hermansah, Tantan (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2023)
Abstract. This research examines the issue of postponing the 2024 election which has gone viral on social media. The Coordinating Minister for Marves claims that 110 million netizens support postponing the 2024 election, in contrast to what the Founder of Drone Emprit shared: 91% are against and 6% are pro for postponing the election. Researchers focus on analyzing advocacy and disseminating the issue of postponing the 2024 election in new public spaces. Previous research agrees that the internet can disseminate election information and influence society, while this research focuses on Twitter and the role of Mafindo and Drone Emprit in mapping issues. Twitter as social media has become a space for unlimited public discussion, election issues have become a widely discussed discourse. This research aims to understand Twitter as a new public space and social changes in society related to the issue of election delays. Researchers use a qualitative approach and case studies, collecting data using interviews, observations, and literature studies, then analyzing and describing them using a critical paradigm. Researchers found that conversations on Twitter were dominated by narratives of criticism and opposition to the postponement of the 2024 elections, not only by the public but also by politicians, legal experts, observers, and high-ranking party officials. The emergence of figures advocating the postponement of the 2024 elections does not affect public opinion. In this case, the typology of internet users falls into two typologies, namely, disseminator and propagandist typologies.